Between Scriptura et Pictura: Meditation on the Domus Dei and the Devotion of the Holy House of Mary - Fallena, Denise (Religions, 2024)
This article examines the representation and significance of the Holy House of Mary as a metaphor for the domus Dei in the initial letters of a 13th-century Book of Hours (Brailes Hours BL MS Add. 49999) using hermeneutics, visual studies, and anthropology of art methodologies. The manuscript delves into the theological implications of the doctrine of the Incarnation and the virginal divine motherhood of Mary depicted in these images. Additionally, it explores the connection between these representations and the devotion to the Holy House of Nazareth and its replica in the sanctuary of Our Lady of Walsingham, recognized as a sacred pilgrimage site. To conduct this analysis, the article considers the figures of the Holy House depicted on pilgrim badges and religious jewels. Specifically, it focuses on the Hylle jewel, whose effectiveness, attributed to its form and materiality, symbolized the aurea palatium Dei.